Kajian Konsep Ambiguitas Ruang Peralihan Pada Kafe Kekinian di Denpasar dan Badung - Giri, Kadek Risna Puspita (Waca Cipta Ruang, 2022)
After the government slowly lifted the social distancing restriction since the pandemic in 2020, the growth of "trendy" café became significant to accommodate the thirst for social interaction. The term "trendy" in the cafe shows that the cafe is following current developments. Trendy cafes have added value in their exterior and interior building to satisfy the visitor's need for taking selfies. One of them is the facade of the building with a terrace located on the front side of the building. The design of these trendy cafes conveys the concept of ambiguity, where it not only serves as a transitional space but also bolster the façade attractiveness. The concept of ambiguity in architecture is to obscure the primary function in a space so that new functions can form new perceptions for visitors. This research aims to determine the design elements that play a role in forming the concept of ambiguity on the terraces of several trendy cafes in Denpasar City and Badung Regency. The method is carried out qualitatively and presented with descriptive analysis. The author analyzes through field observations and documentation and then correlates it with theoretical studies on design elements and ambiguity concepts. Through the study of design elements, it is possible to perceive the design elements that play a role in forming an ambiguity concept of the terrace and presenting new perceptions and impressions of it. Keywords:terrace, facade, ambiguity, cafe